Comparative Analysis of The MOORA Method for Evaluating The Effectiveness of Scholarship Acceptance - Piantari, Ni Kadek Ayuk; Putra, I Nyoman Tri Anindia; Widiastutik, Sri; Kartini, Ketut Sepdyana (Yayasan Sraddha Panca Widya Nusantara, 2024)
The 1945 Constitution regulated the distribution of scholarships to make access to better life opportunities easier. Nevertheless, in some universities the scholarship selection process still depends on conventional criteria to choose the beneficiaries of scholarships; no information technology or decision support system is in place to support the objective selection process. At SMA Negeri 1 Manggis, the application of the Multi-Objective Optimisation on the Basis of Ratio Analysis (MOORA) approach is predicted to improve the effectiveness and objectivity of the scholarship recipient selecting process. Weighting the criteria and normalising the decision matrix produces optimal alternative ranking when applying the MOORA approach to choose scholarship applicants. Following normalisation, a predefined algorithm is used to compute the optimisation value for every alternative student. For ten student possibilities, the computational results show the Yi (Max - Min) values. Then, using these values, one may create a final ranking of the best options, and scholarship recipients can be counselled on the three best options. It is expected that using the DSS approach